Peralihan Hak Kepemilikan Harta Warisan Melalui Perbuatan Melawan Hukum dalam Sistem Kewarisan: (Studi Putusan Mahkamah Agung Nomor 464 K/Pdt/2020) - Richi Shopia Purba; Hasim Purba; Rosnidar Sembiring (CV Rewang Rencang, 2025)
Incidents of unlawful transfer of inheritance rights still frequently occur in Indonesian societal practices. Although the inheritance law system has clearly regulated the mechanism for the transfer of inherited assets, in reality there are still many cases where certain parties attempt to control inheritance through illegal means. The method used in this writing is a normative juridical research method. Analysis of Supreme Court Decision Number 464 K/Pdt/2020 shows that the Panel of Judges was correct in qualifying the unilateral transfer of inheritance land certificates as unlawful acts based on Article 1365 of the Civil Code, but the decision still has weaknesses in providing clarity regarding proportional inheritance distribution mechanisms between adopted children and wives, and does not deeply consider the characteristics of the disputed inheritance property.